CONTROLE QUÍMICO DE Gibberella zea NA CULTURA DA CEVADA - ANTONIAZZI, ANA PAULA (2018)
The objective of this work was to evaluate fungicides, triazole and strobilurin, in the management of Fusarium Head Blight in cultivars of barley, with and without inoculation of the fungus and its effect on agronomic characteristics, quality for malt and in the enzymatic activity in the grain. The experimental design was a randomized complete block consisted a triple factorial (2 x 2 x 3), being: two barley cultivars with high yield ceiling (BRS Brau and MN 6021) associated with and without artificial inoculation of Fusarium graminearum and with three fungicide treatments (Control, Tebuconazole e Azoxystrobin), with three replications totaling 36 plots in the field. They were evaluated characteristics of thousand grain mass, yield, hectoliter weight, protein content, commercial classification and mycotoxin deoxynivalenol (DON). In addition, was calculated the area under the progress curve of the Fusarium Head Blight and the enzymatic activity on the grain. The means were compared by Tukey test, for 5% probability, subsequently; were performed four orthogonal contrasts e estimated the Pearson correlation coefficient, with the level of 5% of significance by t test. The application of fungicide in the spiking of Tebuconazol increased grain yield in the agricultural crop of 2016. The mass of one thousand grains, hectoliter weight, protein content, and commercial classification were not influenced by the management with fungicides in the spiking in the agricultural crops 2016 and 2017. The application of fungicide Azoxystrobin at spiking reduced the area below the curve of progress of giberela in the studied barley cultivars. The application of fungicide to the spiking the Tebuconazole was more efficient in reducing the levels of deoxynivalenol, compared to Azoxystrobin, being this dependent of the crop evaluated. There is a positive correlation of the levels of deoxynivalenol in the grain with the area below the curve of the progress of Fusarium Head Blight in the evaluated barley cultivars. In the BRS Brau and MN 6021 barley cultivars, the activity of the enzymes Superoxide Dismutase, Ascorbate Peroxidase, Catalase, Peroxidase III and Lipoxygenase in the grains were influenced by the application of fungicide on the seedling and artificial inoculation of F. graminearum.